Social networks, terrorism and counter-terrorism: radical and connected - Bouchard, Martin (Contemporary terrorism studies, 2015)
"This book examines two key themes in terrorism studies, the radicalization process and counter-terrorism policies, through the lens of social networks. Despite multiple calls to arms to approach terrorism through the lens of network methods, social networks are still under-researched in terrorism studies. This book aims to show that networks should be at the forefront when analysing terrorists, but also when assessing the responses to their actions. The volume makes a unique contribution by addressing two relatively new themes for terrorism studies. First it puts social network analysis at the forefront - a perspective, and set of methods often identified as crucial to future breakthroughs in the field. Second, the contributions tackle the role of the Internet in the process of radicalization, a highly debated topic in the field today. In addition, the book provides a valuable mix of review essays, critical essays, and original empirical studies, including detailed case studies tracing the transformation of normal individuals into violent radicals. This balanced approach is also found in the topics covered by the authors, as well as their academic disciplines, which include computer science, geography, history, engineering, and criminology as well as political science. Many of the true advances in terrorism studies depend on the successful collaboration of multi-disciplinary teams, each with a different set of methodological and conceptual tools. This book reflects the newfound diversity in this field and is a true product of its time. This book will be of much interest to students of terrorism studies, social networks, security studies, sociology, criminology and IR in general"--